Swedish Plectida (Nematoda). Part 3. The genus Loveninema gen. n. - Holovachov, Oleksandr; Boström, Sven (Zootaxa, 2012)
A new genus Loveninema gen. n., with two new species L. tubulosa gen. n., sp. n. and L. unicornis gen. n., sp. n. is de-scribed from bottom sediments collected in Skagerrak off the west coast of Sweden. Loveninema gen. n. is unique amongother genera of Plectida by possessing a midventral labial projection located on the ventral edge of the oral opening andprotruding anteriorly. Other diagnostic characters include: sclerotised labial framework in the shape of a conoid ring withthree projections extending posteriorly: one mid-dorsal, one left-subventral and one right-subventral; papilliform outer la-bial and cephalic sensilla; amphidial fovea a transverse slit located anterior to cephalic sensilla bases; excretory pore open-ing on the ventral side of the labial region; pharynx uniformly muscular, cylindrical; female reproductive systemdidelphic, amphidelphic; male reproductive system monorchic, with reflexed testis; spicules present; gubernaculum pres-ent or absent; either alveolar or tubular supplements present in males, absent in females; caudal glands and spinneret pres-ent. L. tubulosa gen. n., sp. n. is particularly characterised by the 0.66–1.12 mm long body; short midventral labialprojection; straight vagina without sclerotisations; male without alveolar and with 12–15 tubular supplements, 15.0–21.5µm long spicules, and with gubernaculum. L. unicornis gen. n., sp. n. is particularly characterised by the 0.65–0.98 mmlong body; long midventral labial projection; straight vagina without sclerotisations; male with up to 20 alveolar and without tubular supplements, 11.5–14.0 µm long spicules, and without gubernaculum.